Precautionary recapitalisations: Time for a review - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2017)
The first part of the paper considers the effects of pre-empting a resolution procedure for a troubled financial institution by a precautionary recapitalization as specified in Article 32 (4) (d) of the Bank Recovery and Resolution Directive (BRRD). Benefits are seen for the maintenance of systemically important operations of an institution with legally independent subsidiaries in multiple jurisdictions and possibly for the maintenance of lending in situations where an entire banking system is involved. Other systemic concerns, such as the maintenance of lending when only part of a banking system is affected, the avoidance of damage to money markets, and potential systemic effects from bailing in creditors, can be addressed in a resolution procedure under the rules of the BRRD and do not require the instrument of a precautionary recapitalization. The second part of the paper provides a critical assessment of Article 32 (4) (d) of the BRRD and finds some weaknesses that contribute to raising taxpayers' costs or to reducing the effectiveness of the operation. The availability of precautionary recapitalization outside of resolution contributes to undue and costly delays in acknowledging and addressing problems. The conditions specified in the Directive are problematic, sometimes too tough, sometimes too lenient, most importantly because the objectives of State aid control differ from the objectives of the BRRD. The paper concludes with suggestions for reform.
Keywords: 330